Long-term trends in water transparency of Tibetan Plateau lakes and the response to extreme climate events - Liu, Wangming; Xu, Huan; He, Guowei (Frontiers in Environmental Science, 2024)
Water transparency, as indicated by the Secchi disk depth (Zsd), is a key parameter for assessing the quality of aquatic environments, reflecting the ability of light to penetrate through the water column. In the Tibetan Plateau (TP), where lakes are abundant yet remote and challenging to access, remote sensing techniques offer a promising approach for monitoring Zsd over large spatial scales. In this study, we used the semianalytical -based Zsd algorithm to study the temporal and spatial dynamics of water transparency over TP during the period from 2003 to 2022. The results show that the 173 lakes have a mean value of Zsd is 3.64±2.4 m for long term, and generally with the significantly increasing change trends in the past 20 years. In the central Tibetan Plateau (CTP) region, lake transparency showed a positive correlation with lake surface temperature (r = 0.73) and a negative correlation with precipitation (r = -0.54), highlighting the region's heightened sensitivity to meteorological changes compared to other areas. The spike in water clarity observed in the CTP region may be linked to alterations in lake hydrodynamics driven by the extremely climate events (i.e., El Niño). These results indicated the importance of considering regional climatic factors when interpreting fluctuations in water transparency.